Emotion Regulation in Participants Diagnosed With Attention Deficit Hyperactivity Disorder, Before and After an Emotion Regulation Intervention - Sánchez, Marta; Lavigne, Rocío; Romero, Juan Fco.; Elósegui, Eduardo (Frontiers in Psychology, 2019)
The study of Attention Deficit Hyperactivity Disorder addresses variables related to three core symptoms: inattention, hyperactivity, and impulsivity. However, it has been suggested that in recent years emotional difficulties and subsequent social challenges have not received sufficient attention. This study had two objectives: 1) to compare the performance of participants (age range: 8-14 years) on facial emotion recognition tasks using the Affect Recognition subtest of the Children Neuropsychological Battery II; and 2) to assess the perceptions of family members in relation to variables associated with emotional problems, difficulty in regulating emotions, and anger management using the Spanish Assessment System for Children and Adolescents. Assessments were conducted before and after applying an emotion regulation intervention designed for this study. Following the intervention, there was a significant decrease in scores associated with emotional regulation, and an improvement in the identification of affect on facial recognition tasks. The results suggest that despite Attention Deficit Hyperactivity Disorder children and adolescents having social and emotional deficits secondary to the core symptom triad, emotional regulation in this group can be improved by the application of socio-emotional intervention programs.